The overview of SWOT analysis on MBKM implementation in chinese language education study program FBS UNNES with partner universities and institutions - Anggraeni anggraeni; Retno Purnama Irawati; Rina Supriatnaningsih; Anes Desti Safitri (Universitas Negeri Semarang, 2023)
The MBKM policy, based on regulations from the Directorate General of Higher Education of the Ministry of Education and Culture of the Republic of Indonesia in 2020, is a form of giving autonomous freedom for educational institutions, independence from complicated bureaucracy and also freedom for students to choose their desired program they have wanted to choose. Regarding implementing the MBKM program, the Chinese Language Education Study Program FBS UNNES still encounters many obstacles. (1) Curriculum similarity between study programs or universities. In addition, (2) educational information systems between universities are different and sometimes do not support students and lecturers outside the university. (3) Regarding the partnership, the Chinese Language Education Study Program FBS UNNES has partnered with several universities but has not partnered with more parties. This study aims to analyze the strengths, weaknesses, opportunities and challenges. This qualitative research utilizes a phenomenological research design. Phenomenology in this study refers to the SWOT analysis. The results of the study resulted in 4 SWOT strategies, namely (1) Strengths and Opportunities, (2) Weaknesses and Challenges, (3) Strengths and Challenges, (4) Weaknesses and Opportunities. The most critical strategy that must be carried out is to create a communicative, effective and transparent network system, open a more comprehensive network of relations, provide more opportunities for students and lecturers, and disseminate information about the implementation of MBKM informative and compelling.